Experimental research making methodical errors of analog-digital transformation of random processes - Єременко, В.С.; Вітрук, Ю.В. (Proceedings of National Aviation University (archive), 2005)
The given results of an experimental research a method of statistical modelling of a methodical error of analog-digital transformation random Gauss processes. The received dependences allow to coordinate characteristics of the analog-digital converter to parameters of the measured process.